2008
DOI: 10.1097/01.won.0000335961.68113.cb
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Factors Related to Ostomy Complications and Quality of Life in Veterans With an Ostomy

Abstract: This study found important relationships between demographic and clinical factors and ostomy complications. Skin problems, leakage, and difficulty adjusting predicted total quality of life scores and domains. Establishing relationships among ostomy complications and demographic, clinical factors, and quality of life can enhance identification of patients at risk for the development of complications and is an important first step in identifying the development of effective interventions to reduce the negative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
104
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(126 citation statements)
references
References 9 publications
12
104
1
9
Order By: Relevance
“…1,2,12 In obese patients, the mesentery of their stomas are thicker and shorter, making their stomas particularly at risk for these ischemic events that can result in a retracted stoma. 1,2,6,15 The leakage is even more severe with a retracted stoma where the os is located beneath the abdominal plane. The pooling is so frequent that with an ileostomy in particular, the skin damage occurs quickly and often, and as the skin is exposed to the effluent rich in proteolytic enzymes, increasing the risk for these stomas to progress from simple irritation to advanced wounds.…”
Section: Causes Of Peristomal Skin Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2,12 In obese patients, the mesentery of their stomas are thicker and shorter, making their stomas particularly at risk for these ischemic events that can result in a retracted stoma. 1,2,6,15 The leakage is even more severe with a retracted stoma where the os is located beneath the abdominal plane. The pooling is so frequent that with an ileostomy in particular, the skin damage occurs quickly and often, and as the skin is exposed to the effluent rich in proteolytic enzymes, increasing the risk for these stomas to progress from simple irritation to advanced wounds.…”
Section: Causes Of Peristomal Skin Complicationsmentioning
confidence: 99%
“…Structural characteristics such as stoma type, size, and location on the abdominal plane can affect the seal of the pouching system, and a poor fit can result in leakage and consequently irritation of the skin. 1,2,[6][7][8]11,15,16 Loop ileostomies represent the greatest proportion of peristomal skin complications in patients. In one study, 79% of the patients with a loop ileostomy suffered from a peristomal skin complication.…”
Section: Causes Of Peristomal Skin Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Problems related to ostomies include feelings of embarrassment, 1 sexuality, 2 coping, 3 spirituality,4 and overall HRQOL. 5 We have shown factors that have major roles in HRQOL in this population of patients including ostomy-related complications, 6 and difficulty paying for supplies? We also have found that comorbidities 8 actually may have a larger role in HRQOL than having an ostomy.…”
mentioning
confidence: 99%